KOMUNIKASI ANTARPRIBADI BAGI LANSIA - Paramita, Sinta; Natalia, Debira; Wiryana, Febiola; Emerald, Serena (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2023)
Interpersonal communication is communication that takes place in face-to-face situations between two or more people, either in an organized way or in a crowd of people. Meanwhile, intrapersonal communication or interpersonal communication is communication with oneself with the aim of thinking, reasoning, analyzing and reflecting. The Santa Anna Elderly Home is a homestead or foundation for the elderly that provides services and care so that the elderly can more easily carry out their daily lives, such as bathing, eating, and dressing. This orphanage was founded in 1987 and is located on Jalan Teluk Gong, Gg Mazda 41, Pejagalan, Penjaringan District, North Jakarta City, DKI Jakarta. One of the challenges faced by the Santa Anna Elderly Home is the issue of interpersonal and interpersonal communication among the residents of the orphanage. Not a few of the residents of the orphanage have bad life experiences and feel lonely because they rarely get visits. This problem was exacerbated by the Covid-19 pandemic which lasted for about two years which caused the orphanage to not receive visits from outsiders. Seeing this problem, the PKM team of the Faculty of Communication Sciences, University of Tarumanagara paid a visit to the Santa Anna Elderly Home with the aim of entertaining, developing, and implementing interpersonal and interpersonal communication for the residents of the orphanage. This is realized by a series of simple creative activities that can be a means of interpersonal communication, complemented by entertainment activities that can be a means of interpersonal communication for residents of the orphanage. The implementation of this activity is also supported and enlivened by the Sant'egidio community, a non-profit social community that is quite familiar with the caretakers and residents of the Santa Anna Elderly Home. Komunikasi antarpribadi adalah komunikasi yang berlangsung pada situasi tatap muka antara dua orang atau lebih, baik secara terorganisasi maupun di kerumunan orang. Sementara itu, komunikasi intrapersonal atau komunikasi antarpribadi merupakan komunikasi dengan diri sendiri dengan tujuan untuk berpikir, melakukan penalaran, menganalisis dan merenung. Panti Lansia Santa Anna merupakan wisma atau yayasan untuk orang-orang lanjut usia yang menyediakan pelayanan dan perawatan agar para lansia dapat lebih mudah dalam menjalani kehidupan sehari-hari, seperti mandi, makan, hingga berpakaian. Panti ini didirikan pada tahun 1987 dan berlokasi di Jalan Teluk Gong, Gg Mazda 41, Pejagalan, Kecamatan Penjaringan, Kota Jakarta Utara, DKI Jakarta. Adapun tantangan yang dihadapi oleh Panti Lansia Santa Anna salah satunya adalah perihal komunikasi antarpribadi dan antarpribadi penghuni panti. Tidak sedikit dari penghuni panti memiliki pengalaman hidup yang kurang baik dan merasa kesepian karena jarang mendapat kunjungan. Masalah ini diperkuat dengan adanya pandemi Covid-19 selama kurang lebih dua tahun yang menyebabkan panti tidak menerima kunjungan dari pihak luar. Melihat masalah ini, tim PKM Fakultas Ilmu Komunikasi Universitas Tarumanagara mengadakan kunjungan ke Panti Lansia Santa Anna dengan tujuan menghibur, mengembangkan, dan menerapkan komunikasi antarpribadi dan antarpribadi penghuni panti. Hal ini diwujudkan dengan rangkaian kegiatan pembuatan kreativitas sederhana yang dapat menjadi sarana komunikasi antarpribadi, dilengkapi dengan kegiatan hiburan yang dapat menjadi sarana komunikasi antarpribadi penghuni panti. Pelaksanaan kegiatan ini juga turut didukung dan diramaikan oleh komunitas Sant’egidio, sebuah komunitas sosial non-profit yang sudah cukup familiar dengan pengurus dan penghuni Panti Lansia Santa Anna.